An Efficient Isocyanide‐Based Three‐Component Diastereoselective Synthesis of Chromane‐3, 4‐dicarboxamides. Issue 10 (16th October 2013) - Imanieh, Hossein; Sarlak, Mansooreh; Amanpour, Tayebeh; Bazgir, Ayoob
Abstract An efficient method for the diastereoselective synthesis of chromane‐3, 4‐dicarboxamides via the three‐component reaction of 2‐oxo‐2H‐chromene‐3‐carboxylic acids, amines, and isocyanides in MeCN is reported.